Performance analysis of multiplexed medical data transmission for mobile emergency care over the UMTS channel. - Gallego, J.R.
In this paper, a third-generation universal mobile telecommunications system (UMTS) solution for the delivery of biomedical information from an ambulance to a hospital is presented. The joint transmission of voice, real-time video, electrocardiogram signals, and medical scans in a realistic cellular multiuser simulation environment is considered, taking into account the advantages and particularities of UMTS technology for such transmission. The accomplishment of quality of service constraints for different services is investigated and quantitative results are provided in order to demonstrate the feasibility of using UMTS technology for emergency care services on high-speed moving ambulance vehicles.
Keywords: QoS; UMTS channel; Ambulance; Biomedical information delivery; Cellular multiuser simulation environment; Electrocardiogram signals; Emergency care services; Medical scans; Mobile emergency care; Mobile telemedicine; Multimedia traffic; Multiplexed medical data transmission; Quality of service; Real-tune video; Third-generation universal mobile telecommunications system